2012
DOI: 10.1073/pnas.1115528109
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 fusion oncogenes in high-grade endometrial stromal sarcoma

Abstract: 14-3-3 proteins are ubiquitously expressed regulators of various cellular functions, including proliferation, metabolism, and differentiation, and altered 14-3-3 expression is associated with development and progression of cancer. We report a transforming 14-3-3 oncoprotein, which we identified through conventional cytogenetics and whole-transcriptome sequencing analysis as a highly recurrent genetic mechanism in a clinically aggressive form of uterine sarcoma: high-grade endometrial stromal sarcoma (ESS). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
230
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(240 citation statements)
references
References 26 publications
(23 reference statements)
9
230
0
Order By: Relevance
“…[1][2][3] Histologically, YWHAE-NUTM2A/B endometrial stromal sarcomas are characterized by round to epithelioid cells with scant to moderate faintly eosinophilic cytoplasm and high-grade cytologic features. The nuclei are larger in size and more irregular in contour compared with the tumor nuclei from classic lowgrade endometrial stromal sarcoma and mitoses are readily identified (410 mitoses per 10 high power fields).…”
mentioning
confidence: 99%
“…[1][2][3] Histologically, YWHAE-NUTM2A/B endometrial stromal sarcomas are characterized by round to epithelioid cells with scant to moderate faintly eosinophilic cytoplasm and high-grade cytologic features. The nuclei are larger in size and more irregular in contour compared with the tumor nuclei from classic lowgrade endometrial stromal sarcoma and mitoses are readily identified (410 mitoses per 10 high power fields).…”
mentioning
confidence: 99%
“…Recently, Lee et al 8 identified the genes rearranged in the t(10;17)(q22;p13) translocation previously described in endometrial stromal sarcoma [9][10][11] and also in pediatric clear cell sarcoma of the kidney, 12,13 corresponding to an inframe YWHAE-FAM22 fusion of YWHAE exons 5-2 of FAM22A or FAM22B. 8 The goal of the present study was to analyze the rearrangement of the YWHAE gene by FISH break-apart and RT-PCR techniques, and to identify correlations between YWHAE gene status and morphology, immunohistochemistry (IHC), and clinical behavior in a series of high-grade-morphology endometrial stromal sarcomas with no JAZF1 rearrangements. Given the lack of published data about YWHAE FISH break-apart, 8 we also aimed to identify the optimal threshold for positivity in RT-PCR for cell rearrangements.…”
mentioning
confidence: 99%
“…8 The goal of the present study was to analyze the rearrangement of the YWHAE gene by FISH break-apart and RT-PCR techniques, and to identify correlations between YWHAE gene status and morphology, immunohistochemistry (IHC), and clinical behavior in a series of high-grade-morphology endometrial stromal sarcomas with no JAZF1 rearrangements. Given the lack of published data about YWHAE FISH break-apart, 8 we also aimed to identify the optimal threshold for positivity in RT-PCR for cell rearrangements.…”
mentioning
confidence: 99%
“…The use in recent years of next generation sequencing (NGS) methodology has played an important role in identifying such molecular rearrangements. By way of example, NGS identified a YWHAE‐NUTM 2 fusion brought about by a 10;17‐translocation and a ZC3H7B‐BCOR caused by an X;22‐translocation in ESS, thus adding two new pathogenetic subgroups to this spectrum of tumors 6, 7…”
Section: Introductionmentioning
confidence: 99%